2018
DOI: 10.1590/1806-9061-2016-0444
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and Serum Biochemical Responses of Ovambo Chickens Fed Provitamin A Biofortified Maize

Abstract: Blood profiles, health assessment, indigenous chicken, provitamin A biofortified maize diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(42 reference statements)
1
9
3
Order By: Relevance
“…addition, average erythrocyte size, haemoglobin amount per blood cell, and the amount of haemoglobin relative to the size of the cell per red blood cells were studied. Although, the MCV, MCH and MCHC values reported in this work were lower than broiler normal means values of 174 fL for MCV, 61pg/cell for MCH and 33 g/dl for MCHC reported by Merck (2012) for broilers, it is worthy of note that these values reported in this study are in line with the MCV, MCH and MCHC values reported for broilers by Onunkwo et al (2018), Odunitan-Waya et al (2018, Ifelayo et al (2020) and Muneer et al (2021), and within the normal ranges of 90-140fL (MCV), 33-47 pg/cell (MCH) and 26-35 g/dl (MCHC) reported for broilers by Bounous and Stedman (2000). Hence, the ability of the extracts to maintain the MCV, MCH, MCHC levels of colibacillosis infected broilers indicates that they may possess phytobiotic properties against the E. coli as well as the tendency to restore blood quality.…”
Section: Insupporting
confidence: 82%
“…addition, average erythrocyte size, haemoglobin amount per blood cell, and the amount of haemoglobin relative to the size of the cell per red blood cells were studied. Although, the MCV, MCH and MCHC values reported in this work were lower than broiler normal means values of 174 fL for MCV, 61pg/cell for MCH and 33 g/dl for MCHC reported by Merck (2012) for broilers, it is worthy of note that these values reported in this study are in line with the MCV, MCH and MCHC values reported for broilers by Onunkwo et al (2018), Odunitan-Waya et al (2018, Ifelayo et al (2020) and Muneer et al (2021), and within the normal ranges of 90-140fL (MCV), 33-47 pg/cell (MCH) and 26-35 g/dl (MCHC) reported for broilers by Bounous and Stedman (2000). Hence, the ability of the extracts to maintain the MCV, MCH, MCHC levels of colibacillosis infected broilers indicates that they may possess phytobiotic properties against the E. coli as well as the tendency to restore blood quality.…”
Section: Insupporting
confidence: 82%
“…The higher creatinine on birds fed MSOBD indicates production of more waste products from protein metabolism and muscle contraction(Ileke et al 2014) through kidneys. High creatinine indicates malfunction of kidneys(Odunitan-Wayas et al 2018). However, in this study, high level on MSOBD broilers compared to those offered Control diets could imply lower than optimal functioning of the kidneys.…”
contrasting
confidence: 54%
“…through kidneys. High creatinine indicates malfunction of kidneys(Odunitan-Wayas et al 2018). However, in this study, high level on MSOBD broilers compared to those offered Control diets could imply lower than optimal functioning of the kidneys.…”
contrasting
confidence: 54%
“…Following formulae were used to evaluate the MCV, MCH, and MCHC values (Odunitan-Wayas et al, 2018);…”
Section: Haematological Analysismentioning
confidence: 99%